The World of What-Ifs: The Path to Creating a Novella - Magnea Sif Markúsdóttir 1997- (2025)
This creative writing B.A. thesis in English from the University of Iceland consists of two parts: The novella The World of What-Ifs, which is the result of a creative writing class I attended during my degree and then an exposition. The first chapter in this thesis is written as a continuation of the previous chapters written during the course. With a short synopsis, the aim is that the novella will be able to stand on its own, with a beginning and an end, but without the first four chapters that were part of my final portfolio submitted during the course. The novella is roughly 15,200 words that and consists of a prologue, ten chapters and an epilogue. The exposition is just shy of 4000 words, and it discusses the creative process and the path to the creation of The World of What-Ifs. The essay goes into detail about how the idea came about, my approach and development of the main characters, as well as how they fit into the narrative and the process of plotting a story. In short, it looks at what paths I took towards its creation. The story starts with Bella, who meets Death personified as an old woman in the graveyard where her deceased mother is buried. Death presents Bella with an opportunity to bend fate to her own will and rewrite the past and sends her on a journey. She then meets her reluctant Ghostkeeper, Bill, who is tasked by Death with assisting her on this journey alongside his Ghostkeeper duties of keeping her alive. The permanently grumpy and serious ghost will be her guide and support during this time, as well as making sure she makes it through the next three months and the rest of her life unscathed. Both Bella and Bill will meet their fate head-on and, in the process, learn important life and death lessons.